Design and Analysis of a Smart Blind Stick for Visual Impairment - Zulkhairi Mohd Yusof; Md Masum Billah; Kushsairy Kadir; Muhamad Amirul Sunni Bin Rohim Rohim; Haidawati Nasir; M. Izani; A. Razak (Institute of Advanced Engineering and Science, 2018)
For a long time, visually impaired person uses a white cane to guide their way when travel outside. The white cane has been useful for the blinds in improving their mobility but unfortunately the white cane has its limitation. One of the shortcomings of the white cane is that, it could only detect the obstacles that are within the contact ranges of the white cane. This problem sometimes could cause the blind person to be in trouble because of insufficient time to detect and warn new obstacles in front of the blind person. This research proposes a walking stick system that has two functions; to classify an obstacles height whether it is low or high and to detect a front hole. The ability to detect the height of an obstacle will help the visually impaired to either step over or avoid the obstacle. The ability to detect a hole should help the visually impaired to avoid it in time. The walking stick will use two ultrasonic sensors for the detection of obstacle height, and a laser sensor for the detection of hole. A controller will be used to monitor and analyze the data from the sensors and feedback to the user through a vibration sensor and buzzer. The algorithm to differentiate the height of obstacles is working well and it is able to differentiate high or low obstacles. The laser ranging sensor has successfully been tested for hole detection. Therefore, the walking stick with ultrasonic and laser sensors will help more visually impaired to move around much faster and feeling more safer due to improved warning system for their movement.